2021
DOI: 10.1021/acsami.1c08118
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Free and Efficient Type-II InP/ZnO/ZnS Quantum Dots and Their Application for LEDs

Abstract: It is a generally accepted perspective that type-II nanocrystal quantum dots (QDs) have low quantum yield due to the separation of the electron and hole wavefunctions. Recently, high quantum yield levels were reported for cadmium-based type-II QDs. Hence, the quest for finding non-toxic and efficient type-II QDs is continuing. Herein, we demonstrate environmentally benign type-II InP/ZnO/ZnS core/shell/shell QDs that reach a high quantum yield of ∼91%. For this, ZnO layer was grown on core InP QDs by thermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…Indium phosphide quantum dots (QDs) are a promising alternative to traditional Cd-and Pb-based materials for lighting, displays, and optoelectronic technologies [1][2][3] . However, due to its increased covalency, limitations in easily accessible precursors, and inherent distinctions in precursor reactivity and valency, the synthesis of InP has been met by more challenges when compared to their II-VI counterparts in terms of extracting generalizable design principles and targeted properties 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Indium phosphide quantum dots (QDs) are a promising alternative to traditional Cd-and Pb-based materials for lighting, displays, and optoelectronic technologies [1][2][3] . However, due to its increased covalency, limitations in easily accessible precursors, and inherent distinctions in precursor reactivity and valency, the synthesis of InP has been met by more challenges when compared to their II-VI counterparts in terms of extracting generalizable design principles and targeted properties 4 .…”
Section: Introductionmentioning
confidence: 99%
“…al. 48 and Baskoutas & Terzis 49 , but the curve after imputing deviates in the larger size range The inverse square fitted sizing curve for the data before imputing is (1) and the curve for the data after imputing is (2) where E0 is the band gap in eV and d is the QD diameter in nm. The most likely reason for the deviation in the curves at larger sizes is the limited available data for high quality InP QDs larger than 4 nm.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Indium phosphide quantum dots (QDs) are a promising alternative to traditional Cd-and Pb-based materials for lighting, displays, and optoelectronic technologies [1][2][3] . However, due to its increased covalency, limitations in easily accessible precursors, and inherent distinctions in precursor reactivity and valency, the synthesis of InP has been met by more challenges when compared to their II-VI and IV-VI counterparts in terms of extracting generalizable design principles and targeted properties 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, liquid-state integration allows for sensitive tuning of optical device characteristics by simple injection of QDs, enables suppression of the host-material effect, and keeps a high photoluminescence quantum yield (PLQY) of the QDs in the device architectures. In addition to its benefits for efficiency, liquid-state integration can be advantageous in terms of thermal management of LEDs as well. , The investigation of the remote and liquid-state QD-LEDs showed that liquid can keep the temperature of the device as low as 50 °C, while in remote QD-LEDs, the temperature can elevate to 200 °C, especially at high injection currents . Thus, the usage of QDs in a liquid form in the device architecture keeps the surface temperature low and enhances the device’s reliability .…”
Section: Introductionmentioning
confidence: 99%